The blood lactate and cardiorespiratory responses to upper- and lower-body exercise in cross-country skiers - Hegge, A.; Bolger, C.; Sandbakk, O. (Science and Skiing VI. 6th International Congress on Science and Skiing, Dec. 14 - 19, 2013, St. Christoph am Arlberg, 2015)
The current study aimed to compare the blood lactate and cardiorespiratory responses during upper- and lower-body exercise at different intensities in well-trained individuals. We used cross-country skiers as our subjects since these athletes are endurance trained in both upper and lower extremities, and tested them in upper-body poling and cycling. It was hypothesized that 1) poling would result in higher blood lactate values with an earlier accumulation of blood lactate, and 2) poling would exhibit lower and slower cardiorespiratory responses than cycling when exercising at a given perceived exertion.